Employee costs of corporate bankruptcy - John R. Graham; Hyunseob Kim; Si Li; Jiaping Qiu (Federal Reserve Bank of Chicago, 2022)
An employee's annual earnings fall by 13% the year her firm files for bankruptcy, and the present value of lost earnings from bankruptcy to six years following bankruptcy is 87% of pre-bankruptcy annual earnings. More worker earnings are lost in thin labor markets and among small firms. Ex ante compensating wage differentials for this "bankruptcy risk" are approximately 2% of firm value for a firm whose credit rating falls from AA to BBB, comparable to the magnitude of debt tax benefits. Thus, wage premia for expected costs of bankruptcy are of sufficient magnitude to be an important consideration in corporate capital structure decisions.
Keywords: G32; G33; J21; J31; J61; 330